Currency regulation policy of Kazakhstan in 1990-s (Journal of Economic Research & Business Administration, 2016)
The process of integration of the Republic of Kazakhstan with the world economic space is closely connected with National Bank’s policy in the sphere of currency regulation. That is why analysis of this field is of crucial importance when we study establishing of the country as one of states-leaders of post-soviet space in level of economic development and degree of cooperation with largest international corporations.The article provides description and analysis of currency regulation policy in Kazakhstan in 1990-s as well as evaluation of economic indica-tors of key spheres of the economy of the country by 2000-s, basing on which conclusion regarding the effectiveness of currency regulation policy pursued during mentioned period is made.
Keywords: currency regulation; currency control; economic integration; balance of payments; capital control; capital outflow; capital inflow.